A Comparison of The Effectiveness of Salmonella-Shigella (SS) Agar and Xylose Lysine Deoxycholate (XLD) Agar in Supporting The Growth of Salmonella sp. and Shigella sp. - Ningsih, Ika; Tiro, Kharisma Winnie Chryssantium (UI Scholars Hub, 2026)
Diarrheal diseases caused by Salmonella sp. and Shigella sp. are among the most significant public health challenges worldwide, especially among children. To identify these bacteria, Salmonella-Shigella (SS) and Xylose Lysine Deoxycholate (XLD) agar media are used, which are selective and differential for Salmonella sp. and Shigella sp. Although these media share similar properties and functions for growing Salmonella sp. and Shigella sp., results from previous studies differ from those obtained in tests conducted by the Department of Microbiology, Faculty of Medicine, University of Indonesia. This laboratory-based experimental study used serial dilution with three replicates (triplicate). Based on SNI 2897 of 2008 concerning Standard Plate Count, which is considered valid at 30 -300 colonies, data with a value of 300 will be excluded, and the remaining valid data will be processed using SPSS for Windows version 29. The average growth of Salmonella typhimurium ATCC 14028 on SS agar was 417 × 106 CFU/mL, and on XLD agar was 420 × 106 CFU/mL, a difference that was not statistically significant. Then, the average growth of Shigella sonnei on SS agar was 317 × 106 CFU/mL, whereas on XLD agar it was 183 × 106 CFU/mL, a statistically significant difference. There was no difference in growth effectiveness between Salmonella sp. and Shigella sp. bacteria grown on SS and XLD agar media. Shigella sp. grew more effectively on SS agar.